Contemporary Results of Transcatheter Aortic Valve Replacement in Obese Patients - T. Owais; M. El Garhy; P. Lauten; M. Haensig; H. Lapp; P. C. Schulze; T. Kuntze (Cardiology Research and Practice)
Background. Little research has been conducted to explore the postoperative outcomes of obese patients after transfemoral transcatheter aortic valve replacement (TF-TAVR). Objective. We investigated the influence of body mass index (BMI) on 1-year outcomes after TF-TAVR. Methods. We included retrospectively 1609 high- and intermediate-risk TAVR patients (mean EuroSCORE II 21 ± 11) operated under general anesthesia between March 2014 and March 2018 in central hospital, Bad Berka, Germany. We stratified the patients according to BMI. Results. Our demographic data analysis showed 41% of patients were male and the mean age was 78 (range, 61–92 years). According to the WHO classification, 33% patients had normal weight, 42% were defined as overweight, and 22% were obese. Obese patients showed statistically significant difference in their clinical parameters as having higher incidence of hypertension, diabetes mellitus, pulmonary hypertension, and chronic obstructive pulmonary disease; on the contrary, obese patients were found to be younger than others. We found no differences in valve types and sizes among the different BMI categories. Our mortality rate during the 1-year follow-up period was 17.8% (287 patients). Mortality was significantly higher in patients with BMI < 25 kg/m2 (1 year mortality 149 patients 28.2% in patients with BMI < 25 kg/m2 vs. 138 patients 12.6% in patients with BMI ≥ 25 kg/m2; P=0.0001). Even after considering the confounding risk factors, BMI ≥ 25 kg/m2 was independently associated with reduced 1 year mortality (odds ratio (OR): 0.36, 95% confidence interval (CI): 0.21–0.6; P=0.01) in multivariate logistic regression analysis. The rate of vascular complication was higher in patients with BMI ≥ 25 kg/m2. However, the rate of blood transfusion was higher in patients with BMI < 25 kg/m2. All other serious complications occurred with equal distribution in both groups. Conclusion. In our single-center study, BMI ≥ 25 kg/m2 was independently associated with lower 1 year mortality after TF-TAVR.